Louis Pasteur - Tiner, John Hudson; Nang ChanYeema (Milford, MI USA Mott Media, Inc., 1984)
A biography of the founder of the Missionary Sisters and Brothers of Charity, known for her work with destitute and dying in the streets and slums of Calcutta and other cities.
Keywords: Biography